UNITY OF CONSCIOUSNESS IN MODERN PHILOSOPHICAL AND SCIENTIFIC RESEARCH - Akopov, G.V. (Modern Psychology, 2021)
The article examines the problem of consciousness unity in the context of modern consciousness studies. The article presents various points of view related to different approaches to identification of consciousness and determination of its structure are. The article analyzes the solution to the problem of consciousness unity presented in Tim’s Bayne monograph. In the article we outline the author’s approach to solving the problem of consciousness unity in the logic of social- communicative paradigm and two-factor model of consciousness. The article shows the possibility of a broad actualization of consciousness unity problem not only at the individual level of consciousness, but also in micro-, meso-, macro-group dimensions.